Pengembangan Media Pembelajaran Digital IPA Di SMP N 3 Kecamatan Pangkalan - Riri Okra; Yulia Novera (Jurnal Educative: Journal of Educational Studies, 2019)
Learning media is one of the important components in learning activities. Book as each of the teaching materials must be displayed in accordance with the times and technological developments. Today's smartphone technology has spread throughout the community, including junior high school students. For this reason, efforts need to be made to utilize this smartphone technology to support the learning process. This research is intended to develop teaching materials in the form of e-books or digital books using sigil. This research was carried out using the Four-D model RnD method. This teaching material has been created and validated by media experts in the field of informatics engineering and experts in the field of biology education. After the validation test, the validation value of the media expert is as big as 89,16 And experts in the field of biology education amount to 84,8Media pembelajaran merupakan salah satu komponen penting dalam kegiatan pembelajaran. Buku sebagai salah satu media pembelajaran harus bisa ditampilkan mengikuti perkembangan zaman dan perkembangan teknologi. Teknologi smartphone dewasa ini sudah merambah keseluruh kalangan, tidak terkecuali siswa sekolah menengah pertama. Untuk itu perlu ada usaha yang dilakukan untuk memanfaatkan teknologi smartphone ini untuk menunjang proses pembelajaran. Penelitian ini ditujukan untuk mengembangkan media pembelajaran dalam bentuk e-book atau buku digital menggunakan sigil. Penelitian ini dilaksanakan dengan metode RnD model Four-D. Media pembelajaran ini telah dibuat dan divalidasi oleh ahli media bidang teknik informatika komouter dan ahli bidang pendidikan biologi.  Setelah dilakukan uji validasi didapatkan nilai validasi dari ahli media sebesar 89,16 Dan ahli bidang pendidikan biologi sebesar 84,8